PENGARUH BUDAYA ORGANISASIONAL, MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (STUDI PADA BADAN PUSAT STATISTIK PROVINSI JAWA TENGAH) - UtamiRamadhani, 13.05.51.0103 (Students' Journal of Economic and Management, 2017)
This study to indentify that affect the performance of employees at Badan Pusat Statistik Provinsi Jawa Tengah. these factors are perceived organizational culture, motivation, and work discipline. High perceived organizational can improve employee performance of Badan Pusat Statistik Provinsi Jawa Tengah. This study uses primary data that is questionnaire. The population is 110 employees. Meanwhile the sample 110 respondent. Prior to the analysis, test of validity and reliability of the questionnaire is conducted. Furthermore, hypotheses testing use SPSS version 22. Based on the regression test, it is known that perceived organizational culture, motivation, and work discipline affect positively and significantly on employee performance. The value of r-square is 33,3%. It means that 33,3% of Y variable can be explained by the independent variable. The rest explained by other variables outside of the model. Keywords: Perceived Organizational Culture, Motivation, Work Discipline And Employee Performance